1973
DOI: 10.1021/j100643a022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of photoionization energy on the distance distribution between trapped electrons and N,N,N',N'-tetramethyl-p-phenylenediamine cations in organic glasses

Abstract: Communications to the Editor 3035 ly difficult to determine the angle with precision. This minimum may therefore "correspond" to the 27 and the 2.27 helices at ^75°, -70°for polyglycine.19 Maigret, et al.,20 found the conformation -80°, =: -40°t o be the most stable conformation in their calculation on '-acetyl-N'-methylalanylamide. The local minimum =* -60°, ^60°of approximately 4 kcal/mol of residue obtained for the tetrapeptide of glycine17 has disappeared in the present calculation and this , pair is now o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1975
1975
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 1 publication
1
6
0
Order By: Relevance
“…showed that for a single encounter there exists an upper limit of 60% AML in the remaining disc. However, as Pfalzner (2004) and Moeckel & Bally (2006) showed, consecutive encounters can lead to a significant angular momentum transport.…”
Section: Resultsmentioning
confidence: 99%
“…showed that for a single encounter there exists an upper limit of 60% AML in the remaining disc. However, as Pfalzner (2004) and Moeckel & Bally (2006) showed, consecutive encounters can lead to a significant angular momentum transport.…”
Section: Resultsmentioning
confidence: 99%
“…Giant planets (or their cores) can migrate due to either planetesimal or gas disk interactions (Kley and Nelson 2012). Hydrodynamic simulations of multiple planets interacting with each other and with a surrounding gas disk (Moeckel et al 2008;Marzari et al 2010;Moeckel and Armitage 2012;Lega et al 2013) show that resonant, tightly packed or well-separated systems can form, but the probabilities for these channels cannot be predicted from first principles. Constraints on the dynamics must currently be derived from comparison of the predicted end states with observed systems.…”
Section: Instabilities In Tightly-packed Sys-temsmentioning
confidence: 99%
“…We shall frequently refer to the transverse coordinate ̟ as the impact parameter. Some early results were presented by Moeckel et al (2002).…”
Section: A Hydrodynamical Calculation Of a Wind Colliding With An Impmentioning
confidence: 99%